The SNP rs13147758 in the HHIP Gene Is Associated With COPD Susceptibility, Serum, and Sputum Protein Levels in Smokers - Ortega-Martínez, Alejandro; Pérez-Rubio, Gloria; Ambrocio-Ortiz, Enrique; Nava-Quiroz, Karol J.; Hernández-Zenteno, Rafael de Jesus; Abarca-Rojano, Edgar; Rodríguez-Llamazares, Sebastián; Hernández-Pérez, Andrea; García-Gómez, Leonor; Ramírez-Venegas, Alejandra; Falfán-Valencia, Ramcés (Frontiers in Genetics, 2020)
Background: Genetic association studies have identified single nucleotide polymorphisms (SNPs) related to COPD susceptibility. Aim: to identify HHIP genetic variants associated with COPD, pulmonary function, and serum and sputum HHIP protein levels in Mexican mestizo smokers. Material and methods: Association analysis was performed by carrying out a case-control study in Mexican mestizo smokers comprising two groups: tobacco-smoking subjects with COPD (COPD-TS, n = 222) and smokers without COPD (SWOC, n = 333). We evaluated three SNPs (rs13147758, rs1828591, and rs13118928) in the HHIP gene. Allele discrimination was accomplished by qPCR using TaqMan probes, and determination of protein levels in the serum and sputum supernatants was performed using ELISA. Results: Statistically significant differences were observed in the rs13147758 GG genotype (adjusted p = 0.014, OR=1.95) and the rs13147758-rs1828591 GA haplotype (p=6.6E-06, OR = 2.65) in the case-control comparison. HHIP protein levels were elevated in sputum supernatant samples from the COPD-TS group compared to those from the SWOC group (p=0.03). Based on genotype analysis, HHIP protein levels were lower in the serum samples of rs13147758 GG genotype carriers in the COPD-TS group than in the serum samples of rs13147758 GG genotype carriers from the SWOC group (p<0.05), but there were no differences in the sputum samples. Conclusion: The rs13147758 GG genotype and the rs13147758-rs1828591 GA haplotype are associated with susceptibility to COPD. Furthermore, an association in protein levels was observed between the HHIP rs13147758 genotype and COPD in Mexican mestizo smokers.